2014
DOI: 10.1038/ncomms4867
|View full text |Cite
|
Sign up to set email alerts
|

Conformational targeting of intracellular Aβ oligomers demonstrates their pathological oligomerization inside the endoplasmic reticulum

Abstract: Aβ oligomers (AβOs) are crucially involved in Alzheimer’s Disease (AD). However, the lack of selective approaches for targeting these polymorphic Aβ assemblies represents a major hurdle in understanding their biosynthesis, traffic and actions in living cells. Here, we established a subcellularly localized conformational-selective interference (CSI) approach, based on the expression of a recombinant antibody fragment against AβOs in the endoplasmic reticulum (ER). By CSI, we can control extra- and intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 70 publications
1
69
0
1
Order By: Relevance
“…The finding of intracellular Aβ accumulation in AD retinas, either somatic or perinuclear, suggests an alternate mode of Aβ-mediated toxicity. Recent studies have demonstrated the detrimental effects of intracellular Aβ, by way of oligomerization into pathological forms within the endoplasmic reticulum (88), as well as the formation of neuritic plaques from degenerating neurons containing intracellular Aβ (89).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of intracellular Aβ accumulation in AD retinas, either somatic or perinuclear, suggests an alternate mode of Aβ-mediated toxicity. Recent studies have demonstrated the detrimental effects of intracellular Aβ, by way of oligomerization into pathological forms within the endoplasmic reticulum (88), as well as the formation of neuritic plaques from degenerating neurons containing intracellular Aβ (89).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed to determine the cellular mechanisms of AbO generation, demonstrating that intracellular amyloid bodies can oligomerize into pathological forms through critical conformations formed inside the endoplasmic reticulum (ER). The anti-AbO intrabody selectively intercepts critical AbO conformers and controls their 'toxic' assembly in the ER, without interfering with the complex processes of maturation and processing of APP [147].…”
Section: Glutamate Modulationmentioning
confidence: 99%
“…However, they appear largely not exploitable for subcellular targeting and intracellular functional studies in living cells. In 2014 Meli et al, generated, by an in vivo intracellular selection in yeast cells, a set of conformation-sensitive antibody fragments for different subcellular compartments [147], developing a CSI method. This approach allowed to determine the cellular mechanisms of AbO generation, demonstrating that intracellular amyloid bodies can oligomerize into pathological forms through critical conformations formed inside the endoplasmic reticulum (ER).…”
Section: Glutamate Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence suggesting that oligomers, probably the most neuropathogenic Ab species for disrupting synaptic and cognitive function, play a central role in the onset and progression of AD. [21][22][23] Current data showed that immunotherapy targeting or neutralizing Ab oligomers was effective in protecting cognitive function, and the effects correlated positively with levels of antibodies. [24][25][26] Anti-Ab antibodies incapable of reducing cerebral Ab oligomers failed to attenuate spatial memory deficits in AD model mice.…”
mentioning
confidence: 99%